Kajian analisis bibliometrik tentang pendidikan agama islam: potensial isu untuk studi masa depan di bidang penelitian - Abu Anwar; Alfiah Alfiah; Suhaimi Suhaimi; Arwan Arwan; Syarifuddin Syarifuddin; Miftahuddin Miftahuddin; Arbi Arbi; M. Fahli Zatrahadi; Istiqomah Istiqomah; Darmawati Darmawati (Jurnal Konseling dan Pendidikan, 2022)
Islamic religious education is to equip students with knowledge of Islamic teachings, the history of religious development, Islamic norms and values, and assist them in applying these teachings in everyday life. The purpose of this research is to provide additional knowledge about various studies in the field of Islamic religious education. This research was conducted using a qualitative approach with a bibliometric. The data was taken in 2022 with the number of documents after the limitation of 621 sourced from the Scopus database. Analysis was carried out with the help of openrefine, vosviewer, and Rstudio software. The results of the study show that the most author's countries are Indonesia, Malaysia and followed by the United Kingdom. The most prominent keyword in accordance with the research theme is Islamic religious education. As a popular topic in the future, discussions on education, humanity and research in several places such as Eurasia, Asia and South Asia are predicted to be influential research.